Network programming in .NET with C# and Visual Basic .NET - Reid, Fiach (Amsterdam ; Boston : Elsevier/Digital Press, 2004)
The purpose of this book is to provide tools to design and implement network-orientated applications in .NET. It is also a guide for software designers to choose the best and most efficient way to implement mission critical solutions. The book addresses real-world issues facing professional developers, such as using third-party components as opposed in-house development. It differentiates itself from existing .NET publications because it is aimed at experienced professionals and concentrates on practical, ready-to-use information. The book is written in two languages C# and VB.NET, and covers never-before published information on Telephony in .NET and packet-level networking. This is the second book in the Digital Press Software Development Series. Coverage of lower level protocols allows implementation of performance-centric applications Demonstrates the feasibility of developing telephony solutions in-house rather than outsourcing Written in VB.NET and C# to assist readers working in either language Coverage of Email, FTP and the WWW allows implementation of applications in all three areas.
Understanding the Internet and network programming -- I/O in the .NET framework -- Working with sockets -- HTTP : communicating with Web servers -- SMTP and POP3 : communicating with email servers -- FTP : communicating with file servers -- Securing a network : firewalls, proxy servers, and routers -- Protecting data : encryption -- Controlling user access : authentication and authorization -- Programming for scalability -- Optimizing bandwidth utilization -- Ping, DNS, and WHOIS : monitoring your network -- Analyzing network packets -- Adding digital telephony -- Message queues --IPv6 : programming for the next-generation Internet -- Web services and remoting.
Includes index.
Keywords: Computer networks -- Design and construction; Computer software -- Development; C (Computer program language) -- Study and teaching; Visual Basic (Computer program language); Microsoft .NET.; Microsoft Visual BASIC; Electronic books